Systematic Review of Patient-Centered Needs Assessments Performed by Free Health Clinics - Daniel Jose Arenas; Rommell Noche; Arthur Thomas; Dania Hallak; Swathi Raman (Journal of Student-Run Clinics, 2019)
Background: Free clinics, such as student-run clinics (SRCs), aim to improve healthcare for underserved populations. These populations, which include homeless individuals, low-income citizens, immigrants, and other marginalized groups, have different needs that can also vary by location. It is thus important that SRCs strive to know their patient populations. Needs assessments (NAs) are a tool to achieve this goal. To further develop NAs by SRCs, we sought to synthesize the state of published NAs by free clinics. This manuscript is meant to encourage these clinics to perform more NAs.Methods: We conducted a systematic review of manuscripts containing the concepts â€œstudent clinicâ€ and â€œneeds assessmentâ€. We searched PubMed, Embase, Scopus, Web of Science, and Google Scholar. Manuscripts were included in the review if they 1) were peer-reviewed, 2) described a free-of-charge clinic, 3) performed a NA, and 4) the NA investigated needs or concerns of patients and/or the community. NAs were defined as an approach to gather information about a patient population with the goal of improving their healthcare. Results: The initial search yielded 94 manuscripts; 18 manuscripts met inclusion criteria and were retained for full examination. The NAs showed a plethora of different purposes, methodologies, and useful results. From the analysis, we also present suggestions for future NAs.Conclusions: The existing peer-reviewed and published NAs by student-run clinics show the immense utility and potential of this tool. There is ample opportunity to publish and expand more NAs.